FINANCIAL PLANNING TRAINING FOR MILLENNIALS IN CIJANTUNG VILLAGE: PELATIHAN PERENCANAAN KEUANGAN BAGI MILENIAL DI KELURAHAN CIJANTUNG - Muhammad Faisal; Imelda Sari; Auliffi Ermian Challen (Yayasan Education and Social Center, 2021)
Community Service Activity itself aims to provide insight and knowledge about financial planning, as follows; a. Investment Understanding; b. Personal financial planning; c. MSME financial planning. The targets in this Community Service Program are residents of Cijantung Village, East Jakarta, especially Millennials. In addition, with this program, it is hoped that a more intensive friendship will be established between millennials in the Cijantung village and the Faculty of Economics and Business, YARSI University. In carrying out this community service program, the stages of the planned activities are; first, make an approach with the Karang Taruna Cijantung Village. Second, Implementation of training activities. Third, the final stage of this activity is evaluation and reflection on the success of the activities carried out. Based on the evaluation results, in general, millennials in Cijantung have been able to have good financial behavior. It can be seen that the understanding of millennials has increased after the training was carried out. From this activity, it is hoped that there will be an increase in the understanding of millennials in Cijantung Village regarding financial planning and ways to invest profitably